Protetores solares - Flor, Juliana [UNESP]; Davolos, Marian Rosaly [UNESP]; Correa, Marcos Antonio [UNESP] (Sociedade Brasileira de Química, 2007)
Health problems related to UV radiation can be minimized by the appropriate use of sunscreens. Different kinds of sunscreens are reported in the literature, even though there is a misleading denomination among them and few discussions are presented about how they work. This paper describes some important aspects in order to understand sunscreen phenomena such as: solar radiation effect, type of solar filters, protection mechanism, formulations and solar protection factor (SPF). Moreover the importance of Chemistry and the interdisciplinary studies related to sunscreens and cosmetic researches are emphasized.
Sunscreens
Keywords: sunscreens; SPF; UV-absorbers